Two decades of a protooncogene TBL1XR1: from a transcription modulator to cancer therapeutic target - Du, Ruijuan; Li, Kai; Guo, KeLei; Chen, Zhiguo; Zhao, Xulin; Han, Li; Bian, Hua (Frontiers in Oncology, 2024)
Transducin beta-like 1X-related protein 1 (TBL1XR1) was discovered two decades ago and was implicated as part of the nuclear transcription corepressor complex. Over the past 20 years, the emerging oncogenic function of TBL1XR1 in cancer development has been discovered. Recent studies have highlighted that the genetic aberrations of TBL1XR1 in cancers, especially in hematologic tumors, are closely associated with tumorigenesis. In solid tumors, TBL1XR1 is proposed to be a promising prognostic biomarker due to the correlation between abnormal expression and clinicopathological parameters. Post-transcriptional and post-translational modification are responsible for the expression and function of TBL1XR1 in cancer. TBL1XR1 exerts its functional role in various processes that involves cell cycle and apoptosis, cell proliferation, resistance to chemotherapy and radiotherapy, cell migration and invasion, stemness and angiogenesis. Multitude of cancer-related signaling cascades like Wnt-β-catenin, PI3K/AKT, ERK, VEGF, NF-κB, STAT3 and gonadal hormone signaling pathways are tightly modulated by TBL1XR1. This review provided a comprehensive overview of TBL1XR1 in tumorigenesis, shedding new light on TBL1XR1 as a promising diagnostic biomarker and druggable target in cancer.